Interdigitated back contact silicon heterojunction solar cells featuring an interband tunnel junction enabling simplified processing. (15th November 2018) - Paviet-Salomon, B.; Tomasi, A.; Lachenal, D.; Badel, N.; Christmann, G.; Barraud, L.; Descœudres, A.; Geissbühler, J.; Faes, A.; Jeangros, Q.; Seif, J.P.; Nicolay, S.; et al.
Highlights: An innovative back-contacted c-Si solar cell using a tunnel junction is reported. Nano-crystalline silicon layers are the key enablers of this new device. Up to 23.9% conversion efficiency is demonstrated. Abstract: This paper reports on the development of an innovative back-contacted crystalline silicon solar cell with passivating contacts featuring an interband tunnel junction at its electron-collecting contacts. In this novel architecture, named "tunnel-IBC", both the hole collector patterning and its alignment to the electron collector are eliminated, thus drastically simplifying the process flow. However, two prerequisites have to be fulfilled for such devices to work efficiently, namely (i) lossless carrier transport through the tunnel junction and (ii) low lateral conductance within the hole collector in order to avoid shunts with the neighboring electron-collecting regions. We meet these two contrasting requirements by exploiting the anisotropic and substrate-dependent growth mechanism of n- and p-type hydrogenated nano-crystalline silicon layers. We investigate the influence of the deposition temperature and the doping gas concentration on the structural and the selectivity properties of these layers. Eventually, tunnel-IBC devices integrating hydrogenated nano-crystalline silicon layers demonstrate a conversion efficiency up to 23.9%.